PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA DENGAN KONSEP CBT (COMMUNITY BASED TOURISM) DI DESA LABUAN PANDAN - ARYAWAN ASASANDI, I GUSTI NGURAH; AFZAL, MUHAMMAD (Universitas Mahasaraswati Mataram, 2019)
Tourism is one of the promising business sectors, if local people can see well the potential available around their neighborhood. With the position of the country of Indonesia which is located on the equator which causes diverse types of flora and fauna, as well as the archipelago's topography providing a stretch of both coastal and cultural diversity available, it is no wonder that tourism opportunities are still wide open to be developed. Labuan Pandan Village is a coastal village with 2 (two) dykes in the east, so that it becomes a magnet for tourists who want to see first hand the beauty of coral reefs and mangrove ecosystems. Tourism stretching has begun to be seen in the activity of tourism activists who joined a community called KOMPAK (Labuan Pandan Kreatif Youth Community). The concept of CBT (Community Based Tourism) has been started by the KOMPAK community since 2017 and of course since then the people in Labuan Pandan Village are involved in the tour activities. This study aims (1) To examine the process of empowering local communities with the concept of CBT (Community Based Tourism), (2) Constraints faced by the community in conducting tourism activities with the concept of CBT (Community Based Tourism) in Labuan Pandan Village. This research method uses descriptive method with a qualitative approach; the data used are primary and secondary. Primary data obtained from interviews and observations. The results showed that: (1) Community empowerment activities through village tourism with the concept of CBT (Community Based Tourism) went very well. This is indicated by the high level of community participation in existing tourism activities. This includes preparing accommodation, culinary, cultural arts performances and participating in educational learning activities (Educational Tourism), (2) Constraints faced by the community, that is, they have not mastered fluent foreign languages, so that they are quite inhibiting information disclosure.